Biomechanics of double poling when skiing on snow and using an ergometer - Halonen, J.; Ohtonen, O.; Lemmettylä, T.; Lindinger, S.; Rapp, W.; Häkkinen, K.; Linnamo, V. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The purpose of the present study was to compare cycle characteristics, force production, and muscle activation between double poling on snow and double poling using an ergometer.